2016
DOI: 10.18632/oncotarget.12331
|View full text |Cite
|
Sign up to set email alerts
|

p53 in the mitochondria, as a trans-acting protein, provides error-correction activities during the incorporation of non-canonical dUTP into DNA

Abstract: Mutations in mitochondrial DNA is an outcome of errors produced by DNA polymerase γ during replication and failure of the repair mechanism. Misincorporation of non-canonical dUTP leads to mutagenesis or apoptosis, and may contribute to the cytotoxic effects of 5′-fluorouracil chemotherapy. Tumor suppressor p53 protein in the mitochondria displays physical and functional interactions with mitochondrial DNA and polymerase γ, and by its intrinsic 3′→5′ exonuclease activity can diminish the polymerization errors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The experiments included 10 different damaged 2′-deoxynucleosides (structures are shown in Supporting Information, Figure S4) and 4 cell lines (HeLa, MCF-7, HEK293, and SW620). We found that mitochondrial BER activity in cells increased in the presence of several of the damaged 2′-deoxynucleosides tested (Figure b), apparently as a result of defensive responses to increases in lesions in mtDNA . To further investigate the relationship between the enhanced DNA repair activity and salvage pathways that enable the incorporation of damaged nucleoside into DNA, we tested the effect of a chemical inhibitor of a nucleotide sanitization enzyme for one of the damaged components (dU).…”
Section: Resultsmentioning
confidence: 99%
“…The experiments included 10 different damaged 2′-deoxynucleosides (structures are shown in Supporting Information, Figure S4) and 4 cell lines (HeLa, MCF-7, HEK293, and SW620). We found that mitochondrial BER activity in cells increased in the presence of several of the damaged 2′-deoxynucleosides tested (Figure b), apparently as a result of defensive responses to increases in lesions in mtDNA . To further investigate the relationship between the enhanced DNA repair activity and salvage pathways that enable the incorporation of damaged nucleoside into DNA, we tested the effect of a chemical inhibitor of a nucleotide sanitization enzyme for one of the damaged components (dU).…”
Section: Resultsmentioning
confidence: 99%
“…Towards the last step of the repair process, strand ligation takes place where processed ends of DNA are ligated by LIGIII (DNA ligase III) [166,167]. Numerous other proteins are also implicated in base excision repair including PNKP [145,157,168], PARP1 (poly ADP-ribose polymerase 1) [169][170][171][172], CSB (Cockayne syndrome group B protein) [173,174] and tumour suppressor p53 [175][176][177][178]. However, several investigations have revealed that various alternative DNA repair processes exist in mammalian mitochondria, such as direct reversal (DR), mismatch repair (MMR), and presumably double-strand break repair (DSBR) [3,179].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…p53 in cytoplasm can participate through the intermolecular pathway in a dU-damage-associated repair mechanism by its ability to remove preformed 3′-terminal dUs, thus preventing further extension of 3' dU-terminated primer during DNA synthesis by HIV-1 RT. Similarly, p53 in mitochondria can function as an exonuclease/proofreader for pol γ by either decreasing the incorporation of non-canonical dUTP into DNA or by promoting the excision of incorporated dU from nascent DNA, thus expanding the spectrum of DNA damage sites exploited for proofreading as a trans-acting protein [106].…”
Section: Excision Of Non-canonical Nucleotides By P53 Proteinmentioning
confidence: 99%